The Evolution of Educational Technology Implementation in Elementary School: A Bibliometric Analysis of Scopus Publications from 2010 to 2025 - Kurniawan, Muhammad Ragil; Kuswandi, Dedi; Fajarianto, Otto; Febrilia, Yeyen (The Indonesian Institute of Science and Technology Research, 2026)
The increasing integration of technology in primary education has led to a rapid growth of scholarly publications on educational technology implementation across diverse contexts. However, this expanding body of literature remains fragmented, as it has not been comprehensively examined from an educational technology perspective. The absence of systematic mapping limits a holistic understanding of global research trends in this field. Therefore, this study aims to analyze trends in the implementation of educational technology in primary schools using a bibliometric approach based on Scopus-indexed publications. This study employs a bibliometric research design to systematically map long-term developments over a 25-year period (2000–2025). The methodological framework follows five stages: data retrieval, eligibility screening, data cleaning, bibliometric mapping, and statistical as well as network analysis. Data were collected using the keywords “educational technology” AND “elementary school” and analyzed using VOS viewer (version 1.6.20) and the Bibliometrics R package (version 5.0), with term harmonization applied to ensure analytical consistency. The findings reveal a steady increase in publications, with an annual growth rate of 6.08% and a high coefficient of determination (R² = 0.849), indicating that the field is in a growth phase approaching maturity. A total of 6,125 authors contributed, with an average of 3.74 co-authors per document and an international collaboration rate of 13.55%. Recent keywords highlight digital and AI technologies, while long-standing themes emphasize learning enhancement.